Sejarah Perkembangan Pemikiran Islam dalam Konteks Alam Melayu: Iktibar Untuk Abad Akan Datang - Hj. Yahaya, Mahayudin (Jurnal Usuluddin, 1995)
This article discusses the development of the teaching of Sufism (mysticism) in the Malay Archipalago, and also the influence of Syiah in Malay thought and classical writing.